The Effect of Perceived Usefulness and Perceived Ease of Use on Intention to Use Shopee Paylater with Perceived Trust as a Mediating Variable among Generation Z in Bandung City - Kiagus Muhammad Arsy; Dedi Iskamto (Journal of Business, Social and Technology, 2026)
Background: This research is motivated by the rapid development of Buy Now Pay Later (BNPL) services, especially Shopee Paylater, which is increasingly used by Generation Z in Bandung City. The high adoption of e-commerce and digital payment services highlights the need to understand the factors influencing users’ intention to use Shopee Paylater. Objective: This study aims to analyze the effects of perceived usefulness and perceived ease of use on intention to use Shopee Paylater, with perceived trust as a mediating variable. Methods: This study used a quantitative approach based on the Technology Acceptance Model (TAM). Data were collected through questionnaires distributed to 385 Generation Z Shopee Paylater users in Bandung City and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results: The findings show that perceived usefulness and perceived ease of use have positive and significant effects on intention to use. Both variables also positively and significantly affect perceived trust. Furthermore, perceived trust has a positive and significant effect on intention to use and mediates the relationship between perceived usefulness, perceived ease of use, and intention to use Shopee Paylater. Conclusion: Perceived usefulness, perceived ease of use, and perceived trust are important factors in shaping Generation Z’s intention to use Shopee Paylater. Trust strengthens technology acceptance and supports sustainable fintech service adoption.